The effect of intralingual subtitled video in learning the meaning of targeted English vocabularies in Malaysian ESL secondary school context / Farahiya Zalikha Zakaria and Mohd Azri Abd Jalil - Zakaria, Farahiya Zalikha; Abd Jalil, Mohd Azri (Universiti Teknologi MARA, Pahang, 2022)
Audiovisual materials with captions or subtitles have long been regarded as a great pedagogical tool to enhance language learning such as listening comprehension, oral skills, grammar, and vocabulary. Due to their notable potentials in assisting language learners, the current research thus takes interest on investigating the extent of intralingual subtitled videos in helping ESL students to learn the meaning of the targeted English vocabularies. Underpinned by Paivio's dual-coding theory and Krashen's Input Hypothesis, intralingual subtitled videos become a comprehensive input with multiple modalities that stimulate viewers' information processing system to facilitate better memory retention and recognition of meanings and form of vocabularies. This research employs pre-test and post-test vocabulary quizzes, open-ended questionnaires, and email questionnaires to elicit the data required from 30 ESL Form 2 students of a secondary school in Melaka, Malaysia. Findings indicate that the intralingual subtitled video used does help participants to learn the meaning of the targeted English vocabularies due to the availability of pictorial, textual and audio cues to help participants establish words' meanings. This study offers ESL learners and educators a reference in utilising a multimedia tool that suits learners' needs and interest besides initiating a potential solution to vocabulary-learning issues diagnosed in classrooms.